Enhancement of third-order nonlinear optical properties of HMTA stabilized pure and doped ZnS nanoparticles and their electronic structures - Anand, K. Vijai; Vinitha, G.; Gautam, Sanjeev; Chae, K. H.; Mohan, R.; Asokan, K.; Ravindran, T. R.; Jayavel, R. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
This study reports the third-order nonlinear optical (NLO) properties of hexamethylenetetramine (HMTA) stabilized pure and transition metals (Cu, Co and Mn) doped ZnS nanoparticles (NPs) and their electronic structures. The third-order NLO properties of pure and transition metals (Cu, Co and Mn) doped ZnS NPs were measured by Z-scan technique. From these measurements, the pure and doped ZnS samples exhibit negative nonlinearity i.e., self-defocusing. The open aperture Z-scan measurement shows saturated absorption within the medium. The prepared pure and doped ZnS samples exhibit nonlinear refractive index of the order of 10(-8) (cm(2)/W), nonlinear absorption (NLA) coefficient of the order of 10(-4) cm/W and nonlinear optical susceptibility of the order of 10(-6) esu. The electronic structures of these ZnS NPs were investigated using near edge X-ray absorption fine structure (NEXAFS) measurements at the C K-, N K- and Co L-3,L-2-edges. The C K- and N K-edges XANES spectra reveal the appearance of several spectral features in the range 285-290 eV and 390-430 eV respectively. The Co L-3,L-2-edge NEXAFS spectrum exhibits multiplet absorption lines similar to those of Co2+ ions coordinated in tetrahedral symmetry with four sulfur nearest neighbors. These results clearly demonstrate that divalent Co ions substitute Zn sites. From the Raman spectra, the appearance of multiple resonance Raman peaks indicates that the prepared ZnS samples have good optical quality.